Design method of energy efficiency optimization in PLC-RF wireless transmission networks - Yueyu JIANG; Haoxin CHENG; Kang WANG; Wenjun DAI; Xiaoyu LIU (Dianxin kexue)
An energy efficiency optimization transmission scheme using angular information-based channel state information (AI-CSI) was proposed for indoor communications, which integrated the power line communication (PLC) with radio frequency (RF) wireless communication.Specifically, by considering that the Wi-Fi wireless network and the PLC network were the primary and secondary networks, an optimization problem was established to maximize the total energy efficiency of the secondary network.Then, in order to solve the problem, the beam forming weight vector was obtained by using zero-forcing method based on AI-CSI, and an optimization algorithm joint Dinkelbach with Lagrange multiplier was further presented to achieve the optimal power allocation.Finally, computer simulations were given to verify the effectiveness and superiority of the proposed scheme.Besides, the influence of key parameters such as the number of employed antennas and served users was also analyzed.